Construction grammars : cognitive grounding and theoretical extensions - Östman, Jan-Ola; Fried, Mirjam (Constructional approaches to language, 2005)
The notion 'construction' has become indispensable in present-day linguistics and in language studies in general. This volume extends the traditional domain of Construction Grammar (CxG) in several directions, all with a cognitive basis. Addressing a number of issues (such as coercion, discourse patterning, language change), the contributions show how CxG must be part and parcel of cognitively oriented studies of language, including language universals. The volume also gives informative accounts of how the notion 'construction' is developed in approaches that are conceptually close to, and rel.